Economies of extremes: Lessons from venture‐capital decision making - de Treville, Suzanne; Petty, Jeffrey S.; Wager, Stefan (Journal of Operations Management, 2014)
AbstractAn organization's ability to exploit extreme events—such as exceptional opportunities—depends on its capacity strategy. The venture capital industry illustrates the interplay of expensive capacity and negative externalities from high utilization. The cost of adding a venture capitalist provides a strong incentive to run lean, but such leanness may make it impossible to evaluate all interesting investment opportunities. Using concepts from extreme‐value theory, we analyze the trade‐off between the costs and benefits arising from an increase in the number of evaluated deals. We ground our analysis in 11 years of archival data from a venture capital firm, representing 3631 deals, the decisions made, the reasons for those decisions, and the decision lead times. The firm identified 20% of arriving deals as worth evaluating during the screening process, but was not able to evaluate approximately 9% of those interesting deals due to a lack of capacity. We show that the value of increasing the number of deals evaluated increases with the tail weight of the distribution of deal values. When the right tail is light, increasing the number of deals evaluated may provide too modest a benefit to justify the cost. When, however, the right tail is heavy, the value of increasing the number of deals is likely to more than compensate for the cost of capacity. Our results provide new insight into the relative value of a chase capacity strategy that emphasizes responsiveness versus a high‐utilization heuristic that emphasizes productivity. Our approach can be applied to other search operations such as personnel selection, quality circles seeking to identify root causes, and making employee capacity available for innovation.